About indoeuropean formulaic diction: the reconstruction of a literary language - Rubio Orecilla, Francisco Javier (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
The etymological comparison of formulaic sequcnccs as o.i. svaras...áksitam: gr. κλευ αϕθιτον "imperishable glory" makes possible to reconstruct some literary traces of a extinct language, Proto-Indo-European, whose grammatical system has been reconstructed following a well-defined methodology. By applying this methodology to the formulaic diction of the oldest Indo-European literatures a number of such formulae can be established, and it is also possible to differentiate various stilistic features and mythological subjects; it has also been attempted to reconstruct the Proto-lndo-European meter. Here an updated survey is offered, with the most relevant literature and the results and methodological advances in the last decades.